(untitled) (Innovative professional education, 2022)
Current trends in the development and implementation of innovative technologies in science, technology and society have a direct impact on the entire artistic sphere. Creative industries include design, fine arts, architecture, fashion, writing, publishing, and media. Creative industries play an important role in preparing future performing artists to entrepreneurship, and to increase their competitiveness in the modern labor market of the art industry there is a need to develop entrepreneurial competence.